Drought and famine relationships in Sudan: Policy implications - Teklu, Tesfaye; von Braun, Joachim; Zaki, El Sayed; Ali, Ahmed (International Food Policy Research Institute, 1991)
Sudan is one of the few countries where famine still persists. Why? What are the determinants of famine in Sudan? What is the role of drought, especially in the context of economic policy failure and war? Who is affected by famine? What needs to be done to mitigate and prevent famine? These are some of the questions addressed in Drought and Famine Relationships in Sudan: Policy Implications, Research Report 88, by Tesfaye Teklu, Joachim von Braun, and Elsayed Zaki. The research is particularly concerned with quantitatively tracing the drought-production-consumption-nutrition linkages under famine conditions at the household level in order to identify effective means of alleviating and preventing famine.... while famine is often strongly linked to drought, this research finds that even under the severe economic constraints of Sudan, suitable government planning and action can forestall that linkage.